Graphite in an archaeological context comparing to other black substances – research problems and prospects - Trąbska, Joanna (Analecta Archaeologica Ressoviensia, 2020)
In the archaeological context, substances with a black color have been extensively used in many ancient communities, in the form of items and layers, with the use of biogenic and mineral substances, and requiring a separate methodological approach. Each of them behaves differently in technological and postdepositional processes. The potential degree of the complexity of intentionally applied layers (e.g. paints or cosmetics) and the overlap of secondary substances and crusts, increases difficulties in obtaining unambiguous results and their interpretation. Graphite plays an important role among them. Several areas of the current use of graphite are, or at least could be, commonly shared in the present and in the past, and thus their analysis could be inspiring for archaeology and archaeometry. Graphite fingerprint and potential fingerprints are discussed in terms of their variability. The problem of graphitization as a potential source of misleading interpretation is discussed.